The Feasibility Study of Rectangular Floating Solar Panel Motion in Semangka Bay Waters - Adietya, Berlian Arswendo; Gunawan, Yudy; Zakki, Ahmad Fauzan; Mursid, Ocid; Tuswan, Tuswan (Institut Teknologi Sepuluh Nopember, 2025)
With the depletion of mineral resources in Indonesia, the need for effective renewable energy alternatives has become critical. Solar energy, harnessed through photovoltaic panels, presents significant potential. However, the widespread adoption of solar panels remains limited due to their large land area requirements and susceptibility to damage. Floating solar panels, installed on water surfaces, offer a promising solution by enhancing energy efficiency through natural cooling while addressing land constraints. This study aims to analyze the motion dynamics of floating solar panels in Semangka Bay and identify the most effective design for open water conditions. Three models were tested: rectangular, kite-shaped, and perforated, using 3D simulation software. The analysis focused on the Response Amplitude Operator (RAO) under regular wave conditions at a 180° angle. The results revealed that Model 3, with 8 mooring points, exhibited the best performance in mitigating rolling, pitching, and heaving motions. The maximum rolling value reached 826.24 cm at 81 seconds, with a minimum of -735.36 cm at 86.7 seconds. Pitching peaked at 390.30 cm at 61.4 seconds and fell to -376.42 cm at 63.9 seconds. Heaving values ranged from a maximum of 17.64 cm at 62.8 seconds to a minimum of -220.94 cm at 83 seconds. This study concludes that Model 3 with 8 moorings offers superior stability, making it the optimal design for floating solar panels in open waters like Semangka Bay. By addressing environmental and implementation challenges, this research contributes significantly to advancing floating solar energy technology in Indonesia. The findings highlight the potential of efficient and resilient designs to harness Indonesia’s abundant solar energy resources effectively.